2000
DOI: 10.1073/pnas.080010897
|View full text |Cite
|
Sign up to set email alerts
|

The mutated human gene encoding hepatocyte nuclear factor 1β inhibits kidney formation in developing Xenopus embryos

Abstract: The transcription factor hepatocyte nuclear factor 1␤ (HNF1␤) is a tissue-specific regulator that also plays an essential role in early development of vertebrates. In humans, four heterozygous mutations in the HNF1␤ gene have been identified that lead to early onset of diabetes and severe primary renal defects. The degree and type of renal defects seem to depend on the specific mutation. We show that the frameshift mutant P328L329fsdelCCTCT associated with nephron agenesis retains its DNA-binding properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 42 publications
2
89
1
Order By: Relevance
“…However, transfecting low amounts of Y352 expression vector, the transactivation potential of the mutant is lower compared with the wild type, whereas at higher amounts, the mutant reaches the transactivation potential of the wild type ( Figure 3B). We previously found a similar behavior for the mutant P328L329, although in this case, at high input, the mutant was even more active than the wild type, suggesting a gain of function mutation (15). To compare directly the transactivation potential between the two mutants, we transfected HeLa cells with increasing concentrations of either of these expression vectors.…”
Section: Mutants Differ In Their Transactivation Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…However, transfecting low amounts of Y352 expression vector, the transactivation potential of the mutant is lower compared with the wild type, whereas at higher amounts, the mutant reaches the transactivation potential of the wild type ( Figure 3B). We previously found a similar behavior for the mutant P328L329, although in this case, at high input, the mutant was even more active than the wild type, suggesting a gain of function mutation (15). To compare directly the transactivation potential between the two mutants, we transfected HeLa cells with increasing concentrations of either of these expression vectors.…”
Section: Mutants Differ In Their Transactivation Potentialmentioning
confidence: 99%
“…The expression vector encoding human HNF1␤ wild-type, P328L329del CCTCT, and R137-K161del have been described (15). The additional HNF1␤ mutations were made by site-directed mutagenesis (Quick Change site-directed mutagenesis kit; Stratagene, La Jolla, CA) on the myc-Rc/CMVHNF1␤ construct using the following primer pairs: S151P, 5'-CGCACCTCCCCCAGCATC-3', 5'-GAT-GCTGGGGGAGGTGCG-3'; E101X, 5'-CTCAACACCTAGGAGGC-GG-3', 5'-CCGCCTCCTAGGTGTTGAG-3'; R177X, 5'-CAGAAAGC-AATGAGAGATC-3', 5'-GATCTCTCATTGCTTTCTG-3'; P159delT, 5'-CAAGGGCACCCCATGAAGACCCAG-3', 5'-CTGGGTCTTCAT-GGGG-TGCCCTTG-3'; Q243delC, 5'-CCC-GCGTCCAGCAAATC-3', 5'-GATTTGCTGGACGC-GGG-3'; A263insGG, 5'-GAGAGAGAGG-GGCCTTAGTGGAGG-3', 5'-CCTCCACTAAGGC-CCCTCTCTCTC-3'; Y352insA, 5'-GAGTGCGCTAACAGCCAGCAG-3', 5'-CTGCTG-GCTGTTAGCGCACTC-3'.…”
Section: Plasmid Constructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found the S36F mutation in a Japanese MODY family and functional analysis showed that it was a gain-of-function mutation [43]. It has been reported that overexpression of wild-type HNF-1b in Xenopus embryos leads to impaired development of the pronephros [44].…”
Section: Hnf-1b Diabetesmentioning
confidence: 99%
“…Gain-of-function could be a third mechanism, although its pathogenesis of impaired insulin secretion is not known. Recently, it has been reported that a frameshift mutation (P328L329fsdelCCTCT), identified in a European MODY5 family with renal abnormalities, acts as a gain-of-function mutation (~twofold) [8]. Thus, S36F mutation in the HNF-1b gene might affect the clinical phenotypes in this MODY family.…”
mentioning
confidence: 99%